Association between Achilles Tendon Injury and Daily Activities Performance in Athletes and Non-Athletes after 1 Month of Injury: Achilles Tendon Injury and Daily Activities Performance - Tariq, Arsalan; Mousavi Zadeh, Sayed Alireza; Nazarian, Seyedeh Kimia; Ismail, Ahmed; Waheed, Waleed bin; Komitaki, Mina Bayati (Pakistan Journal of Health Sciences, 2023)
Achilles tendon injuries are significant because they affect the mobility of the lower extremities, which is important in both sports and daily life. This research aims to shed light on the more general effects of these injuries on people's functional capacities. Objective: To determine the association between Achilles tendon injury and daily activities performance in athletes and non-athletes after 1 month of injury. Methods: A cross-sectional analytical study was conducted at the university of Lahore and Punjab stadium Lahore over a four months periods from January to April 2019. A total of 30 subjects male were approached by the non-probability convenient sampling method. Fisher exact test was applied to identify the associated factors. P-value ≤ 0.05 counted as significant. Results: Results showed symptoms of Achilles tendon injury effect daily activities of athletes and non-athletes. Majority of athletes who participated in study have stiffness in foot as compared to non-athletes. According to results there is association between ankle/foot giving away during strenuous activity (p-value 0.0025), during moderate activity (p- value 0.005) and in light activity (p value-0.006) in both athletes and non –athletes. Conclusions: Both athletes and non-athletes were facing difficulties during activities and cause negative impact on activities of participants after one month of injury.